Correlation of calorie intake with 24-hour urinary urea nitrogen level changes in critically ill patients at RSUI Depok, Indonesia - Githa Putri Puspita Sari; Witjaksono, Fiastuti; Sutanto, Krisadelfa; Singal, Anna Maurina (World Nutrition Journal, 2024)
Calorie together with protein intake has been proven to be important factors that play a role in critically ill patients. Hypermetabolism in the early acute phase increases energy expenditure and calorie requirement. Insufficient calorie intake will increase protein degradation for gluconeogenesis, which can be assessed by the level of 24-hour urinary urea nitrogen (UUN). Adequate daily calorie intake is expected to improve the UUN level in patients. This study aims to investigates the correlation of calorie intake with UUN level changes in critically ill patients.